Deradikalisasi Islam dalam Perspektif Pendidikan Agama - Qodir, Zuly (Jurnal Pendidikan Islam, 2013)
Physical or non physical terrorism is a form of radicalization that is considered the most extreme for applying new methods of relative in radicalization religion. The ideological war which is considered as the most advanced form of radicalization is a continuation of the religious world and the radicalization of form since 2000 in Indonesia. To reduce the various forms of religious radicalisation, the formal education is developed in Indonesia. The religious radicalization is a variant of the extreme movement that could be detrimental to Muslim in Indonesia based on data of literature, media studies and field observations.